Sino-US Competition and Challenges for Global Political Order - Prof. Dr. Iram Khalid (Journal of Political Studies, 2019)
As the world would call it, China is the 2nd superpower in the world and this fact is making headlines. With this shift of power, China is being seen as reshaping the world order. While China negated this fact in the beginning, four years later China presented itself as establishing ‗new power relations.‘ What are the ground realties? How does China want the world to see itself? How the United is States challenging an emerging China and where are we heading towards is the emphasis of this paper. The first part, China makes headlines, provides a brief insight into how China is making inroads as a major actor, pushing itself towards a reformist agenda while making sure that its selfinterest is not damaged. Mearsheimer‘s theory of neo-realism is studied in this regard. In the second part of the part, the strategic relationship of South Asian states, post 9/11 has been studied with respect to the theory of balance of power, with United States and India vs Pakistan and China Strategic Quadrangle. It is concluded that in comparison to United States and India, Pakistan and China‘s strategic partnership presents itself as a hallmark of ‗Grand Security Strategy.‘ In the third part of the paper, with reference to the strategy of Bandwagoning and Balancing, scholarly discussion by Robert Ross, David Shambaugh and David Kang is detailed. The authors discuss the insecurities of Southeast Asian states and the balance they are trying to maintain between United States and China. They argue that ‗balance of influence‘ is being maintained, evading the concept of balance of power. Fourthly, the paper debates the world of economic interdependence and states (US and China) which will dominate the 21st century. It relates this factor with specific reference to the European states, since their economies have majorly been at stake. The paper is limited to studying Sino-U.S. Competitions and Changes for the Global Political Order in the region of South Asia and European States. Conclusively, placing China into an international order does not come by choice, instead it is a necessity. Henceforth, U.S. needs to ensure that China is not seen as a disruptive but a positive force with which international affairs have to be restructured and balanced.